Why Cancer Cells Crave Sugar: A Review: Mengapa Sel Kanker Sangat Membutuhkan Gula: Sebuah Ulasan - Sadiq, Dina H. (Indonesian Journal on Health Science and Medicine, 2025)
In addition to causing weight gain, eating too much sugar raises the risk of obesity and diabetes, both of which raise the chance of cancer. It turns out that while eating sugar does not always cause cancer, it can cause the disease because of the way it affects your waist. Sugar is necessary for cancer cells to survive, not to proliferate and divide. Although this sugar is absorbed by all bodily tissues, it is more readily absorbed by tissues with higher energy requirements, such as cancer cells. Because of this, some people have concluded that sugar accelerates the growth of cancer cells. "I'd be shocked if cutting back on sugar didn't help lower the risk of cancer," she says. "High-fructose corn syrup, which is found in soft drinks, sweetened teas, sports drinks, and processed meals, as well as in candy, cookies, ice cream, and sweetened breakfast cereal, should be avoided. Highlights: Excess sugar raises obesity and diabetes risk, increasing cancer risk. Cancer cells absorb more sugar due to higher energy needs. Avoid high-fructose corn syrup in processed and sugary foods. Keywords: cancer, cells, crave, sugar